Spatial and temporal gene expression patterns during early human odontogenesis process - Yu, Yejia; Wang, Kun; Wang, Zhuo; Cai, Haoyang; Liao, Chengcheng; Wu, Yutao; Zhang, Jingyi; Tian, Weidong; Liao, Li (Frontiers in Bioengineering and Biotechnology, 2024)
Studies on odontogenesis are of great importance to treat dental abnormalities and tooth loss. However, the odontogenesis process was poorly studied in humans, especially at the early developmental stages. Here, we combined RNA sequencing (RNA-seq) with Laser-capture microdissection (LCM) to establish a spatiotemporal transcriptomic investigation for human deciduous tooth germs at the crucial developmental stage to offer new perspectives to understand tooth development and instruct tooth regeneration. Several hallmark events, including angiogenesis, ossification, axonogenesis, and extracellular matrix (ECM) organization, were identified during odontogenesis in human dental epithelium and mesenchyme from the cap stage to the early bell stage. ECM played an essential role in the shift of tooth-inductive capability. Species comparisons demonstrated these hallmark events both in humans and mice. This study reveals the hallmark events during odontogenesis, enriching the transcriptomic research on human tooth development at the early stage.